Situational factors affecting rugby sevens match performance. Issue 4 (2nd October 2019) - Henderson, Mitchell J.; Fransen, Job; McGrath, Jed J.; Harries, Simon K.; Poulos, Nick; Coutts, Aaron J.
ABSTRACT: Purpose : To examine the independent influence of a range of situational factors on physical and technical match performance during international rugby sevens matches. Methods : Data was collected from 20 professional rugby sevens players from one team across one competitive season. Activity profiles were measured using wearable microtechnology devices, and technical performance measures were collected using match video analysis. A principal components analysis was conducted to reduce the dimensionality of the physical and technical match performance variables into single index values incorporating each variable's distinct information. Linear mixed models were then constructed to examine the collective influence of external contextual factors on physical and technical index scores. Results : Increased points conceded, a winning match outcome, and more favourable weather all had positive impacts on the Physical Performance Factor, with all other situational factors examined not contributing to a significantly better model fit. Technical Performance Factor values were shown to increase with longer match involvement durations and decrease when playing against higher ranked opponents. Conclusions : These findings show that winning the match, conceding more points, and more favourable weather conditions are associated with increased physical performance; whilst technical performance improved with longer playing durations and playing lower ranked opponents.